STUDI GEOLOGI DAERAH TIHENGO DAN SEKITARNYA KECAMATAN PONELO KEPULAUAN KABUPATEN GORONTALO UTARA - Hidayansya, Taufik; Arifin, Yayu Indriati; Akase, Noviar (Universitas Negeri Makassar, 2024)
The research titled Geology of the Tihengo Area and Surroundings, Ponelo Kepulauan District, North Gorontalo Regency was conducted with the aim of understanding the geomorphological, stratigraphic, and geological structural conditions of the area using geological survey or mapping methods. Based on the research findings, the Tihengo area and its surroundings are located at an elevation of 0-125 meters above sea level, featuring varied morphology ranging from lowlands to steep hills. The region is predominantly comprised of residential, agricultural, and plantation lands, with vegetation generally classified as sparse to moderate. The relief in this area includes plains to steep hills with